The experience of competition ban following a positive doping sample of elite athletes - Georgiadis, E.; Papazoglou, I. (Journal of Clinical Sport Psychology, 2014)
World Anti-Doping Association (WADA) is responsible for doping-free sporting contests and is the only sporting body posing relevant competition sanctions. While doping relates to various controversial attitudes and beliefs proposed in the past, the confirmation of a competition ban following a doping violation has many negative connotations for the lives of the athletes. This can elicit multiple significant and far-reaching implications for them and their close ones. Aiming to better understand these implications in an athlete`s life, 5 Greek male and female athletes having recently received a competition ban after a doping violation were interviewed. Qualitative analysis of the data showed that many important psychological, social, and financial implications follow such a sanction. Most importantly, these consequences may even contribute to indications of poor mental and physical health. Discussion of the results provides suggestions for the alleviation of the negative consequences following an involuntary sporting career pause or termination.